Kolaborasi Keterbukaan Informasi dalam Pengelolaan Arsip Pandemi COVID-19 pada Pemerintah Kota Malang - I Gede Eko Putra Sri Sentanu; Muhammad Rosyihan Hendrawan; Klara Kumalasari; Muhammad Edo Edi Sriyono; Tri Hardika Sri Jaya Negara (Department of Public Administration, Universitas Negeri Surabaya, 2022)
This research aims to describe collaborative information disclosure in managing the COVID-19 pandemic archives in the Malang city government. Public information disclosure is a means of optimizing public oversight of state administration. Information Disclosure is critical to realize Good Governance in encouraging good governance. This study uses a descriptive qualitative approach. Data collection techniques were carried out using in-depth and structured interviews, non-participatory observation and documentation. Selection of informants using purposive sampling with certain considerations that are relevant to the research topic. The results of this study describe the collaboration concept of information disclosure in the management of the COVID-19 pandemic archives at the City Government of Malang with an analysis using the collaboration concept framework of Ansell and Gash. Information disclosure collaboration in the management of the COVID-19 pandemic archives at the Malang city government has not gone well. The stakeholders involved in the management of the COVID-19 pandemic archives are only limited to government stakeholders.